Taxas de indução do KHI na obtenção de haploides em função de diferentes texturas de grãos de milho - Baleroni, Alessandra Guedes (2014)
The production technology of doubled haploids (DH) stands out in programs of maize breeding due to the possibility of reducing the time to obtain lines. Furthermore, the manpower and the necessary financial resources are also lower compared to the conventional method. Obtaining DH plants is basically the induction of haploid, followed by duplication of the genetic content of haploid possible. For this, a preliminary identification of haploids is essential. The objectives of this study were to obtain haploid seeds of different genotypes, verify the efficiency of the separation of potentially haploid seed by staining anthocyanin assigned by R1-nj gene and analyze the rate of haploid possible in function of grain texture. Plants of inducer KHI were crossed in vivo with four hibrids F1?s. Seeds resulting from these crosses were characterized as to haploid through morphological marker R-navajo. The seeds selected as possible haploids from four ears, chosen each genotype were sown in a greenhouse for a confirmation based on phenotype of plants. About 50 ears of each genotype were obtained. Seeds with dent endosperm showed better pigmentation, facilitating the selection via R-Navajo. However, this selection is not fully efficient given that rate of haploid possible based on this selection, was reduced significantly after the evaluation of the phenotype of the plants, indicating the presence of selected false positives by expression of anthocyanin, assigned the R1-nj gene.